Teaching methodology in logistics courses for business administration programs [Metodología de enseñanza en cursos de logística para programas de administración de empresas] (2019)
This article aims to present a teaching methodology based on learning-doing and service-learning approaches for logistics training in business managers. This with the aim of responding to the real needs of companies and allowing the appropriation of knowledge and skills offered in undergraduate university courses. Through student surveys, it is determined that the proposed methodology is relevant and consistent for use in the professional practice. The methodology develops competencies to solve real problems in companies, and also strengthens and puts into practice the knowledge learned in logistics management and other subjects of business administration. © 2019, Centro de Informacion Tecnologica.